Impact of resuspended mine tailings on benthic biodiversity and ecosystem processes: The case study of Portmán Bay, Western Mediterranean Sea, Spain. (15th May 2022) - Gambi, Cristina; Canals, Miquel; Corinaldesi, Cinzia; Dell'Anno, Antonio; Manea, Elisabetta; Pusceddu, Antonio; Sanchez-Vidal, Anna; Danovaro, Roberto
Abstract: Industrial seabed mining is expected to cause significant impacts on marine ecosystems, including physical disturbance and the generation of plumes of toxin-laden water. Portmán Bay (NW Mediterranean Sea), where an estimated amount of 60 Mt of mine tailings from sulphide ores were dumped from 1957 to 1990, is one of the most metal-polluted marine areas in Europe and worldwide. This bay can be used to assess the impact on marine ecosystems of particle settling from sediment plumes resulting from mine tailings resuspension. With this purpose in mind, we conducted a field experiment there to investigate subsequent effects of deposition of (artificially resuspended) contaminated sediments on (i) prokaryotic abundance and meiofaunal assemblages (in terms of abundance and diversity), (ii) the availability of trophic resources (in terms of organic matter biochemical composition), and (iii) a set of ecosystem functions including meiofaunal biomass, heterotrophic C production and C degradation rates. The results of this study show that mine tailings resuspension and plume deposition led to the decline of prokaryotic abundance and nematode's biodiversity. The later decreased because of species removal and transfer along with particle resuspension and plume deposition. Such changes were also associated to a decrease of the proteins content in the sediment organic matter, faster C degradation rates and higher prokaryotic C production. Overall, this study highlights that mine tailing resuspension and ensuing particle deposition can have deleterious effects on both prokaryotes and nematode diversity, alter biogeochemical cycles and accelerate C degradation rates. These results should be considered for the assessment of the potential effects of seabed mineral exploitation on marine ecosystems at large. Graphical abstract: Image 1 Highlights: Mine-tailings resuspension cause the decline of nematode biodiversity. Particle-loaded plumes reduce the nutritional quality of the sedimentary organic matter. Sediment resuspension stimulates C degradation rates and higher prokaryotic C production. Mine tailings resuspension alters biogeochemical processes in marine ecosystems.